Photo-decolorization and ecotoxicological effects of solar compound parabolic collector pilot plant and artificial light photocatalysis of indigo carmine dye. (February 2015) - Saggioro, Enrico Mendes; Oliveira, Anabela Sousa; Buss, Daniel Forsin; Magalhães, Danielly de Paiva; Pavesi, Thelma; Jimenéz, Margarita; Maldonado, Manuel Ignacio; Ferreira, Luis Filipe Vieira; Moreira, Josino Costa
Abstract: The aim of this study was to analyze the photocatalytic degradation of C.I. Food Blue 1 under artificial and solar irradiation using titanium dioxide and to evaluate the ecotoxicity of the photodegradation products in organisms of two different food chain levels. Three different artificial-light and geometric photoreactors were evaluated for the ideal amount of catalyst and UV-light time irradiation. The optimized experiments were performed in a solar compound parabolic collector pilot plant with different water matrices (distilled water, freshwater, synthetic and real MWWTP) at Plataforma Solar de Almería. Photodegradation of the indigo dye was followed by UV–Vis spectroscopy, high performance liquid chromatography, total organic carbon and ion chromatography. Solar pilot plant photocatalysis was efficient for different water matrices but the photodegradation was found to be somewhat slower for the more complex matrixes. Ecotoxicological evaluation with Daphnia similis and Pseudokirchneriella subcapitata showed that photodegradation products were more toxic than untreated indigo carmine and that titanium residues affected the two tested species. Highlights: Solar CPC pilot plant photocatalysis was very fast and simulated the real situations of environmental remediation. Evaluated at different water matrices photocatalyis is necessary due to the presence of different ions that acted as scavengers. Photoproducts were more toxic than untreated dye for Daphnia similis and Pseudokirchneriella subcapitata . Nano-TiO2 residues affected both species and may potentiate toxicity of photoproducts. Results highlight the importance of evaluating photoproducts toxicity and of after treatment removal of TiO2 traces.